Strategies for learning English vocabulary among middle basic education students, school year 2024-2025 - Salas Solano, Carla Jimena (2025)
Vocabulary is a fundamental aspect of achieving English proficiency, as it significantly influences overall language skills. Despite its critical role, observations during classes and practicum revealed that students face significant vocabulary deficiencies. This highlights the need to understand the strategies they use to learn vocabulary. Consequently, the purpose of this curricular integration work is to investigate the strategies used by middle basic education students at a private institution in Loja during the 2024-2025 school year. Two sub-research questions were developed: one focusing on identifying the most commonly used strategies for learning English vocabulary, and the second one on describing the obstacles faced by middle basic education students. To address this research, a mixed-method approach was employed, combining quantitative data from a questionnaire with qualitative insights from classroom observations. Specifically, the study involved 18 students and 2 teachers from a private institution, with data collection conducted over a three-week period. These participants were selected through convenience sampling. The findings revealed that cognitive and memory strategies, which include playing word games (Scrabble, Hangman), learning spelling rules, flashcards, writing sentences with new words, listening to podcasts or videos, and practicing stress and intonation were the most frequently employed strategies. The obstacles identified were the opportunity to practice vocabulary in authentic contexts, the limited use of technology, and adaptation of vocabulary instruction to learners' needs. In conclusion, this study highlights the importance of integrating interactive tools, real-life applications, and personalized approaches to enhance vocabulary learning. Consequently, it is recommended that educators and policymakers incorporate these strategies into the English language curriculum to improve vocabulary acquisition and overall language proficiency in similar educational settings